Medical Imaging 2019: Image Processing 2019
DOI: 10.1117/12.2512393
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of a pipeline of unsupervised retina image analysis methods with a CNN

Abstract: A pipeline of unsupervised image analysis methods for extraction of geometrical features from retinal fundus images has previously been developed. Features related to vessel caliber, tortuosity and bifurcations, have been identified as potential biomarkers for a variety of diseases, including diabetes and Alzheimer's. The current computationally expensive pipeline takes 24 minutes to process a single image, which impedes implementation in a screening setting. In this work, we approximate the pipeline with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In addition, knowledge distillation is used as a technique to prevent overfitting. With knowledge distillation, knowledge from a large model is transferred to a model with less parameters [38, 39], a strategy that has been shown to be useful in image classification [40], biomarker approximation [41], and image segmentation [42].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, knowledge distillation is used as a technique to prevent overfitting. With knowledge distillation, knowledge from a large model is transferred to a model with less parameters [38, 39], a strategy that has been shown to be useful in image classification [40], biomarker approximation [41], and image segmentation [42].…”
Section: Methodsmentioning
confidence: 99%
“…7 In previous work we showed that these biomarkers can be approximated with a deep learning approach. 12 In this study we investigated the added value of these biomarkers for the training process of a deep learning model that directly classifies fundus images.…”
Section: Related Workmentioning
confidence: 99%
“…We compared five different strategies: (1) random initialization; (2) ImageNet weights; (3) model pretrained on global retinal microvascular measurements (T2D biomarkers), including vessel caliber and vessel tortuosity; 12 (4) A multi-target learning (MTL) approach with random initialization and (5) Multi-target learning with ImageNet weights. For the T2D biomarker approach (3) we first trained a model to predict four microvascular measures as described elsewhere 12 and then replaced the output layer for the classification task. For the multi-target approaches (4 and 5), we simultaneously predicted four T2D biomarkers and T2D status.…”
Section: Model Setup and Initializationmentioning
confidence: 99%